1982
DOI: 10.1042/bj2020561
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of β-endorphin-related peptides in rat pituitary and brain

Abstract: beta-Endorphin, the most potent known naturally occurring analgesic agent, is found in pituitary and brain in company with a series of structurally and biosynthetically related peptides that are essentially devoid of opiate activity. In studies of beta-endorphin it is important to discriminate between the active and inactive forms of the peptide. This review describes the use of chemical and immunological methods for localizing the peptides in the tissues, extracting and resolving the peptides by chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(37 citation statements)
references
References 53 publications
1
36
0
Order By: Relevance
“…Using this antibody, we observed a characteristic distribution of immunoreactivity (11,27) between PD and NIL, which demonstrates that N-acetylation of endorphins in tilapia akes place in the melanotropes exclusively. Overall, the HPLC results confirm the idea (15) that the synthesis and processing of endorphin in teleosts resemble that in mammals (35). A promi nent intracellular product coeluted with N-ac-END( 1-31), which probably served as a precursor for the other products.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Using this antibody, we observed a characteristic distribution of immunoreactivity (11,27) between PD and NIL, which demonstrates that N-acetylation of endorphins in tilapia akes place in the melanotropes exclusively. Overall, the HPLC results confirm the idea (15) that the synthesis and processing of endorphin in teleosts resemble that in mammals (35). A promi nent intracellular product coeluted with N-ac-END( 1-31), which probably served as a precursor for the other products.…”
Section: Discussionsupporting
confidence: 82%
“…The major intracel lular product may represent tilapia N-ac-/3-END( 1 -26), a sug gestion supported by the HPLC elution profile of Xenopus laevis NIL /3-endorphins (31). In the rat also, N-acetylated /3-endorphin ( 1 -26), , and (1-31) are the major intracellular en dorphins in the NIL (35). It is unlikely that the novel endorphin like molecules recently postulated to occur in rainbow trout (25) would be detected by the antibody presently used.…”
Section: Discussionmentioning
confidence: 87%
“…Gel exclusion of β-endorphin-related peptides extracted from regions of rat brain showed that lipotropin was only a minor component; the majority of the peptides had the approximate molecular size of β-endorphin. The β-endorphin-related peptides were identified by extraction from the tissues and ion-exchange chromatography, the amounts being determined by radioimmunoassay (Smyth & Zakarian 1982, Zakarian & Smyth 1982b. Two distinct processing patterns were apparent: the first was characteristic of the hypothalamus, midbrain and amygdala, and the second of the hippocampus, brainstem and colliculi (Fig.…”
Section: β-Endorphin In the Brainmentioning
confidence: 99%
“…In order to assess changes in endogenous brain ␤-endorphin secretion, a local microdialysis method was utilized which has recently been shown to accurately indicate CNS responses to noxious stimuli such as formalin (Zangen et al 1998). The microdialysis site selected, the hypothalamic arcuate nucleus, is the primary, nearly exclusive, source of ␤-endorphin in the CNS, and ramifies extensively throughout the brain, with particularly dense innervation in pain modulatory regions of the periaqueductal gray and brainstem, and along the walls of the adjacent third ventricle (Bach 1997;Bloom et al 1978;Zakarian and Smyth 1982).…”
Section: Discussionmentioning
confidence: 99%
“…In order to assess changes in endogenous brain ␤-endorphin secretion, a local microdialysis method was utilized which has recently been shown to accurately indicate CNS responses to noxious stimuli such as formalin (Zangen et al 1998). The microdialysis site selected, the hypothalamic arcuate nucleus, is the primary, nearly exclusive, source of ␤-endorphin in the CNS, and ramifies extensively throughout the brain, with particularly dense innervation in pain modulatory regions of the periaqueductal gray and brainstem, and along the walls of the adjacent third ventricle (Bach 1997;Bloom et al 1978;Zakarian and Smyth 1982).Previous studies in our and other laboratories have demonstrated that transplants of adrenal medullary chromaffin cells into the subarachnoid space of the spinal cord can attenuate pain responses in a variety of animal models and offers a promising avenue for clinical pain management (Brewer and Yezierski 1998;Buchser et al 1996;Burgess et al 1996;Décosterd et al 1998;Hains et al 1998;Hama and Sagen 1993;Lazorthes et al 1995;Ortega-Alvaro et al 1997;Sagen et al 1990;Siegan and Sagen 1997;Vaquero et al 1991;Winnie et al 1993;Yu et al 1998). Although the transplanted cells appear to produce some of their antinociceptive effects via local release of pain-reducing analgesic agents, including catecholamines and opioid peptides, into the host spinal CSF (Sagen and Kemmler 1989;Sagen et al 1991), recent studies have indicated that these transplants can also produce neuroplastic changes in the pain processing circuitry of the spinal cord, including restoration of spinal inhibitory neurons and decreased c-fos activation in response to persistent pain (Ibuki et al 1997;Sagen and Wang 1995).…”
mentioning
confidence: 99%